Effect of fine bubbles for washing of monolith type porous ceramic membranes treating oil-in-water emulsions. (October 2022) - Hashimoto, Kurumi; Onzuka, Atsushi; Nishijima, Wataru; Yamazaki, Masashi; Aoki, Michiko; Sao, Tomomi
Abstract: Produced water generated in the recovery of crude oil contains oil and high concentrations of salts, organic matter, and suspended solids and must therefore be treated appropriately prior to disposal. Monolithic ceramic membranes have high oil removal rates and have the advantage of being compact, having a long life, and withstanding chemicals, heat, and high cleaning pressures. Membrane fouling, however, is a significant drawback to membrane filtration. Scrubbing using air bubbles generated by a diffuser is generally used to physically clean membranes. However, monolithic ceramic membranes cannot be scrubbed using air bubbles because their fluid channels are only a few millimeters wide. Membrane washing efficiency was therefore evaluated using fine bubbles smaller than the diameter of the channels. In dead-end filtration, flushing the membrane surface with air-microbubble water or air–ultra-fine bubble (UFB) water after backwashing and air-blowing (conventional cleaning) of the channels was more efficient than conventional cleaning. Flushing with UFB water was not influenced by changes in pH that changed the zeta potential of the UFB. Membrane fouling was suppressed in crossflow filtration by mixing UFB water with feed water. There was no significant change in the diameter of the oil droplets in the feed water before and after UFB mixing. The ZP of the oil droplets peaked at around −20 mV before UFB mixing. However, the peak shifted to around −25 to −29 mV after UFB mixing. Graphical abstract: Image 1 Highlights (85 characters): A fouled ceramic membrane was cleaned by microbubble (MB) and ultra-fine bubble (UFB). In dead-end filtration, MB or UFB flushing was more efficient than conventional cleaning. UFB flushing was not influenced by changes in pH that changed the zeta potential of the UFB. Membrane fouling was suppressed in crossflow filtration by mixing UFB water with feed water. Zeta potential of oil droplets with UFB shifted more negative than that without UFB.